2010
DOI: 10.4062/biomolther.2010.18.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Constituents Isolated from Ulmus davidiana var. japonica

Abstract: -Twenty six compounds (1-26) were isolated from the root barks of Ulmus davidiana var. japonica. The anti-inflammatory activity of the isolated compounds were evaluated against the generation of inflammatory chemical mediators in bone marrow-derived mast cells. Among them, compounds 10, 11, 13, 15 and 19 inhibited not only cyclooxygenase-2 dependent prostaglandin D2 generation but also 5-lipoxygenase dependent leukotrien C 4 generation in a concentration-dependent manner. In addition, compounds 11, 12, 13, 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(25 reference statements)
0
10
1
Order By: Relevance
“…The anti-inflammatory activity of friedelin (2) was reported by the carrageen induced paw edema method (Shimizu and Tomoo, 1994). Although, friedelin (2) was reported to be inactive against 5-LOX dependent LTC 4 formation in bone marrow derived mast cells (Zheng et al, 2010), our results showed that the compound (2) indeed had a stronger inhibition of the SBL enzyme. Sailer et al (1996) reported that pentacyclic triterpenes with keto group were crucial for their inhibition of 5-LOX.…”
Section: Resultscontrasting
confidence: 66%
“…The anti-inflammatory activity of friedelin (2) was reported by the carrageen induced paw edema method (Shimizu and Tomoo, 1994). Although, friedelin (2) was reported to be inactive against 5-LOX dependent LTC 4 formation in bone marrow derived mast cells (Zheng et al, 2010), our results showed that the compound (2) indeed had a stronger inhibition of the SBL enzyme. Sailer et al (1996) reported that pentacyclic triterpenes with keto group were crucial for their inhibition of 5-LOX.…”
Section: Resultscontrasting
confidence: 66%
“…In fact, while phenolic compounds are generally described as prominent plant-derived inhibitors of 5-LOX product synthesis [28,30], individual constituents identified in stem bark extract can directly contribute to the observed inhibitory effects. Specifically concerning monomeric flavan-3-ols, it is worth referring to the effects upon 5-LOX dependent leukotriene C 4 (LTC 4 ) production in bone marrow-derived mast cells upon treatment with catechin ( 2 ) (20 µM), mediating 99.8% inhibition [31], being also reported to inhibit potato 5-LOX activity (IC 50 value of 16.5 µg/mL) [32]. Relevantly, catechin ( 2 ) happens to be one of the main active compounds found in flavocoxid, an FDA-approved medical food for the treatment of osteoarthritis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies on chemical characterization demonstrated polyphenolic catechins as major bioactives of the RUE [ 16 , 42 , 43 ]. Accordingly, we analyzed the eight major catechins in the RUE using HPLC and LC/MS ( S1 Fig ), and we could detect only catechin that is reported as one of major bioactive antioxidant compounds in the RUE [ 16 , 42 , 43 ]. In addition, the catechin compound has been reported as a bioactive compound with antioxidant effect and thus protective against alcohol-induced liver injury in rats through suppression of ROS-mediated NF-kB signaling pathways [ 44 ].…”
Section: Discussionmentioning
confidence: 99%